An appetite for meat? Disentangling the influence of animal resemblance and familiarity - Possidónio, C.; Piazza, J.; Graça, J.; Prada, M. (Appetite, 2022)
Consumers in modern society are often less exposed to meat that resembles the animal, and thus are less familiar with it, making it difficult to disentangle the influence of these two inputs (familiarity vs. animal resemblance) on meat appetite. Across three studies, we sought to systematically disentangle the impact of familiarity and animal resemblance on meat appetite using inductive (Study 1) and experimental (Studies 2a-2b) approaches. In Study 1 (N = 229) we separated familiarity and animal resemblance into orthogonal dimensions using 28 meat products. Participants provided free associations and rated the products on familiarity, animal resemblance, and appetitive appeal. In Studies 2a and 2b (N = 514) we experimentally examined the independent contributions of familiarity and animal resemblance, using stimuli normed in Study 1. We hypothesized that animal resemblance has its most pronounced influence on appetite when meat products are unfamiliar. Participants’ free associations and ratings of the products were in line with this conditional hypothesis (Study1), as were the experimental manipulations of familiarity and animal resemblance (Studies 2a-2b), confirmed by a mini meta-analysis. In all three studies, familiarity had a pervasive influence on appetite. These findings suggest that product familiarity can attenuate the psychological impact that animal reminders have on appetite. Thus, interventions aimed at eliciting animal associations with meat should consider the familiarity of the products employed.